ИССЛЕДОВАНИЕ МИКРОКЛИМАТА ГОРОДА С ЦЕЛЬЮ ОЦЕНКИ БИОМЕТЕОРОЛОГИЧЕСКИХ ПОКАЗАТЕЛЕЙ СЕЛИТЕБНОЙ ТЕРРИТОРИИ (Географический вестник=Geographical bulletin, 2017)
Рассматриваются различные показатели биометеорологической оценки территории, которые могут быть уточнены при использовании результатов микроклиматических наблюдений. Проведенные исследования позволяют планировать наиболее рациональное освоение территории (жилая застройка, рекреационные зоны и др.).К л ю че в ы е с л о в а: микроклимат; направление и скорость ветра; температурный режим территории; биометеорологическая оценка территорииRESEARCH OF THE MICROCLIMATE OF CITY WITH THE PURPOSE OF THE ESTIMATION OF BIOMETEOROLOGICAL PARAMETERS OF INHABITED TERRITORY In article various parameters of a biometeorological estimation of territory which can be specified at use of results of microclimatic supervision are considered. Carried out researches allow to plan the most rational development of territory (a housing estate, recreational zones, etc.).K e y w o r d s: microclimate; a direction and speed of a wind; a temperature mode of territory; a biometeorological estimation of territory.